Answer:
G = 1
h = 2
Step-by-step explanation:
4(2h - 3) - 5h = -6
8h - 12 - 5h = -6
3h - 12 = -6
3h = 6
h = 2
g = 2(2) - 3
g = 4 - 3
g = 1
Answer:
Step-by-step explanation:
3x + 3 + 3x - 1 = 3x + 8
6x + 2 = 3x + 8
3x + 2 = 8
3x = 6
x = 2
HJ= 3(2) + 8 =6 + 8 = 14
HI= 3(2) - 1 = 6 - 1 = 5
IJ = 3(2) + 3 = 6 + 3 = 9
You subtract the ones place, then the tens, and lastly the hundreds place. Your answer will be 184 if you are looking for the answer as well.
Answer:
(A) Question 1
Step-by-step explanation:
Answer:
how this helps
Step-by-step explanation: